2019
DOI: 10.1152/ajpgi.00300.2018
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal TGR5 agonism improves hepatic steatosis and insulin sensitivity in Western diet-fed mice

Abstract: Takeda G protein-coupled receptor 5 (TGR5) agonists induce systemic release of glucagon-like peptides (GLPs) from intestinal L cells, a potentially therapeutic action against metabolic diseases such as nonalcoholic steatohepatitis (NASH), nonalcoholic fatty liver disease (NAFLD), and Type 2 diabetes. Historically, TGR5 agonist use has been hindered by side effects, including inhibition of gallbladder emptying. Here, we characterize RDX8940, a novel, orally administered TGR5 agonist designed to have minimal sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…Similar to FXR, TGR5 activity can regulate glucose and lipid homeostasis. Several in vivo studies in mice have suggested that TGR5 activation by synthetic agonists could improve insulin and glucose tolerance as well as liver and pancreatic function [82], decrease plasma triglycerides and LDL-cholesterol [83], and ameliorate hepatic steatosis [84]. However, controversial results have been reported with a TGR5 KO mice model, as TGR5 KO female mice gained much more body weight and accumulated more fat mass under HFD feeding, while TGR5 knockout male mice did not show significant difference in body weight gain or fat mass accumulation when compared to the wild-type control [85].…”
Section: Role Of Bile Acid Signaling Through Fxr and Tgr5mentioning
confidence: 99%
“…Similar to FXR, TGR5 activity can regulate glucose and lipid homeostasis. Several in vivo studies in mice have suggested that TGR5 activation by synthetic agonists could improve insulin and glucose tolerance as well as liver and pancreatic function [82], decrease plasma triglycerides and LDL-cholesterol [83], and ameliorate hepatic steatosis [84]. However, controversial results have been reported with a TGR5 KO mice model, as TGR5 KO female mice gained much more body weight and accumulated more fat mass under HFD feeding, while TGR5 knockout male mice did not show significant difference in body weight gain or fat mass accumulation when compared to the wild-type control [85].…”
Section: Role Of Bile Acid Signaling Through Fxr and Tgr5mentioning
confidence: 99%
“…Treatment of HFD-fed mice with INT-777 decreased plasma free fatty acids and liver steatosis, liver fibrosis and plasma AST and ALT levels [9]. Similarly, the TGR5 agonist, RDX8940, was shown to decrease liver weight and hepatic triglyceride and cholesterol levels in mice fed a Western diet [27]. Moreover, dual agonists of TGR5 and FXR protect against NAFLD.…”
Section: Tgr5 and Hepatic Lipid Metabolismmentioning
confidence: 96%
“…Previous work has also shown that whole body Tgr5 −/− mice fed a HFD are more insulin-resistant than Tgr5 +/+ mice, as assessed by an insulin tolerance test [25]. Furthermore, TGR5 agonists have been shown to ameliorate glucose intolerance and improve insulin resistance in obese and diabetic mice [9,13,[27][28][29]48]. Treatment of diet-induced obese (DIO) mice with INT-777, a semi-synthetic TGR5 agonist, has been shown to promote GLP-1 secretion from L-cells, improve insulin sensitivity in liver and muscle and decrease hepatic glucose production [9].…”
Section: Tgr5 and Glucose Regulationmentioning
confidence: 99%
See 2 more Smart Citations